Sustainable community- based safe water options to mitigate the Bangladesh arsenic catastrophe - an experience from two upazilas - Jakariya, Md.; Chowdhury, AMR; Hossain, Zabed; Rahman, Mizanur; Sarkar, Quaiyum; Khan, Ruhul Islam; Rahman, Mahfuzar (BRAC Research and Evaluation Division (RED), 2019)
Sustainable community-based safe water options have been successfully operating in two upazilas involving 531 villages and encompassing a population of 497,488. Testing of tubewells for arsenic was carried out on a census basis by trained village health workers (VHWs) using the Merck fieldtesting kit. A total of 51,685 tubewells were tested and further verified both in the field and laboratory. VHWs initially identified suspected arsenicosis patients who were later confirmed by physicians. A total of 403 patients were identified. The prevalence rates of arsenicosis were 106/10,000 in Sonargoan and 57/19,000 in Jhikargachha upazilas. The average age of the patients was 36 and 30 years respectively and the majority belong to the 15-45 years age group. There has been close community involvement at all stages of implementation of the arsenic-free safe water options adapted from various sources, giving preference to the community-based options to ensure local participation and utilize knowledge. Potential sources of arsenic-free drinking water were identified. To ensure sustainable use provided options were assessed based on community acceptability, technical viability, and financial viability. The key to the success of the project has been the combination of close integration with the community at all stages and appropriate technical solutions.